25 The usefulness of the existing guidelines for performance of endomyocardial biopsy in patients with suspected myocarditis and related outcomes in a contemporary era. (30th September 2020) - Murphy, L; McGuckin, M; Giblin, G; Keogh, A; McGovern, B; Fabre, A; O'Neill, J; Mahon, N; Joyce, E
Abstract : Introduction: Diagnostic endomyocardial biopsy (EMB) in patients with myocarditis helps to direct therapy and guide prognosis. The original 2007 joint scientific statement provided guideline indications based on unique clinical scenarios, detailing who should undergo this invasive investigation but have not been studied in a contemporary cohort of suspected myocarditis patients. Purpose: To investigate the correlation between the clinical guideline indications for EMB and the presence of a diagnostic biopsy result and associated outcomes in patients with suspected myocarditis in a national quaternary referral center. Methods: All cases of suspected myocarditis referred to the National Advanced Heart Failure and Transplant Center between 2009–2019 were identified through pathological records. A thorough retrospective chart review was then performed on all patients. Outcomes including need for inotrope or mechanical circulatory support (MCS), heart transplantation and in-hospital mortality were recorded. Results: In total, 25 (68% male, mean age of 45 ± 15 years) EMBs were performed for suspected myocarditis between 2009–2019, 64% (n=16) of which demonstrated diagnostic results. Clinical characteristics of those with histologically confirmed myocarditis are represented in figure 1 . Regarding pathologic subtypes, 81% (n=13) identified an acute lymphocytic myocarditis, 13% (n=2) giant cell myocarditis and one patient (6.3%) eosinophillic myocarditis. The majority of those with a histologically confirmed myocarditis had a Class I or IIa guideline indication for EMB (n=12, 75%). All patients requiring inotropes and/or MCS (n=9) and/or heart transplant (n=3) were in this group. The remaining 4 patients (25%), of whom three were diagnosed with acute lymphocytic myocarditis and one an immune checkpoint inhibitor (ICI) myocarditis, either met Class IIb criteria (n=2) or would not have been accounted for in this guideline. Four patients (25%) died during the index admission, one of whom was in the latter group (histologically confirmed myocarditis without a 2007 guideline indication). Conclusions: In this National referral sample, 75% of patients with suspected myocarditis had a Class I or IIa indication for EMB, reinforcing the usefulness of these guidelines even in a contemporary era. Further, existing guideline indications appeared to identify a sicker group of patients more frequently requiring inotropes, MCS and/or heart transplant. However, in the contemporary era, 25% of patients had either none or a less well established indication for EMB despite a subsequent confirmed histological diagnosis, including a case of immune checkpoint inhibitor myocarditis, which has emerged since the publication of the 2007 guidelines. This highlights the need for clinical suspicion and correlation outside of accepted clinical scenarios.